PREEMPTING PLAINTIFF CITIES - Swan, Sarah L (The Fordham urban law journal, 2018)
Within the city-state relationship, states hold an enormous amount of power. Recently, states have been using that power to pass extremely aggressive preemption laws that prohibit cities' regulatory efforts on many fronts. These new preemption laws most commonly occur in the context of red states limiting the regulatory scope of blue cities, inflaming those already tense city-state relationships and cutting into what many view as the appropriate scope of local autonomy.